Analisis SWOT untuk Pengembangan Potensi dan Peluang Pasar pada Gama Private Center - Nadya Lutfiana Putri; Ayu Sulasari; Rizky Kurniawan Murtiyanto (Jurnal Media Administrasi, 2024)
SWOT analysis is one of the well-known tools for situation analysis of the company's internal and external environment. SWOT analysis is often used as a reference for strategic planning by maximising strengths and taking opportunities by minimising weaknesses and avoiding threats. This research was a descriptive qualitative research using SWOT analysis as an evaluation. This study used data collection techniques of observation, interviews, and questionnaires. The sampling technique used was purposive sampling techniques. The number of respondents was 9 respondents who were owners, employees, teachers, and students of Gama Private Center. The results of the SWOT analysis found 5 points in each factor. It is known that the internal value is positive 2.42 and the external factor is positive 1,90. The position of the Gama Private Centre is in quadrant I.